2019
DOI: 10.1158/0008-5472.can-18-3668
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR-328–3p Impairs Cancer Stem Cell Function and Prevents Metastasis in Ovarian Cancer

Abstract: Cancer stem cells (CSC) play a central role in cancer metastasis and development of drug resistance. miRNA are important in regulating CSC properties and are considered potential therapeutic targets. Here we report that miR-328–3p (miR-328) is significantly upregulated in ovarian CSC. High expression of miR-328 maintained CSC properties by directly targeting DNA damage binding protein 2, which has been shown previously to inhibit ovarian CSC. Reduced activity of ERK signaling in ovarian CSC, mainly due to a lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 54 publications
1
43
2
2
Order By: Relevance
“…Multiple miRNAs have been reported to be involved in stemness maintenance and vascularity formation [35][36][37] . MiR-200c, miR-638, and miR-371-5p have been reported to regulate SOX2 in CRC [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple miRNAs have been reported to be involved in stemness maintenance and vascularity formation [35][36][37] . MiR-200c, miR-638, and miR-371-5p have been reported to regulate SOX2 in CRC [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Oct4, Nanog and ALDH [78] miR-23a PTEN/PI3K/Akt [79] miR-494-3p NOTCH1-PI3K [80] miR-19a/19b Wnt/β-catenin [81] Mir-21 Nanog-Stat-3 [113] miR-145 ADAM17, SOX9 [114] miR-200c ALDH1, Nanog, Oct4, SOX2. [115] Ovarian miR-328 ERK [116] miR-20a miR-200c PI3K/AKT [117] miRNA-34c-5p EGFR-ERK [118] miR-92a Wnt [119] miR-1207 Wnt/β-catenin [120] miR-17 LKB1-p53-p21/WAF1 [121] miR-136 NOTCH3, NF-kB, Cyclin D1, Survivin, BCL-XL, BCL2 [122] Thyroid miR-21 ABCG2, Oct4 [123] miR-148a ATC-CSCs [124] Further, we have also elaborated how miRNAs modulate signaling pathways associated with CSCs and highlighted that exclusive targeting of the dysregulated miRNAs can be of great therapeutic significance in human cancers ( Figure 3).…”
Section: Role Of Mirna and Oncogenic Signaling Pathways In Human Cancmentioning
confidence: 99%
“…Furthermore, the underlying mechanism suggested that low-level ROSs in ovarian CSCs is the main cause of the downregulation of ERK signaling which led to miR-328 overexpression and degradation of DDB2. Thus, targeting of ROS-ERK-miR-328-DDB2 or mir-328 may lead to eradication of ovarian CSCs and overall clinical improvement in the OC patients [116]. EMT, an important phenomenon associated with stemness-related tumor aggressiveness, has been shown to enhance stemness of OC, and miR-20a and miR-200c can regulate EMT in OC through the regulation of the PI3K/AKT pathway [117].…”
Section: Other Human Malignanciesmentioning
confidence: 99%
“…A frequency of CSCs present in a given tumor population can be analyzed in limiting dilution assay (LDA) by transplanting increasing dilutions of single tumor cell suspensions. LDA analysis in vivo is the gold standard to determine the CSC frequency in a given tumor cell population (50,51). In addition to LDA, subsequent transplantation assays provide an important information about the long-term self-renewal and tumor regeneration capacity of the tentative CSC populations (52).…”
Section: The Cancer Stem Cell or Hierarchical Modelmentioning
confidence: 99%